2018
DOI: 10.1111/bdi.12658
|View full text |Cite
|
Sign up to set email alerts
|

Double trouble: Weekend sleep changes are associated with increased impulsivity among adolescents with bipolar I disorder

Abstract: These findings highlight the important effect of sleep on impulsivity among adolescents with BD and add to the growing evidence that establishing sleep routines may be an important therapeutic target for youth with BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…‘Circadian function’ and ‘Chronobiological treatments’ in section 6.1.) but especially so when tackling bipolar depression, because of the significant role that chronobiological mechanisms are thought to play in the pathogenesis of bipolar disorder (Gershon et al, 2019). Healthy diet and exercise also help institute routines and normalise sleep (e.g.…”
Section: Management Of Bipolar Disordermentioning
confidence: 99%
“…‘Circadian function’ and ‘Chronobiological treatments’ in section 6.1.) but especially so when tackling bipolar depression, because of the significant role that chronobiological mechanisms are thought to play in the pathogenesis of bipolar disorder (Gershon et al, 2019). Healthy diet and exercise also help institute routines and normalise sleep (e.g.…”
Section: Management Of Bipolar Disordermentioning
confidence: 99%
“…For example, longer latency period and more frequent awakening during the night were associated with depressed mood, while the variability in sleeping duration was related to impulsive behaviour. (22) Hence, further studies should evaluate whether sleep quality in type II bipolar disorder can influence the progression of the disorder. In our research, the risk in adolescents for type I bipolar disorder and type II was not significantly associated with poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“… 76 Another recent study in 13‐ to-19-year‐olds diagnosed with bipolar disorder (BD; n = 33, 16.2 years), the change in sleep duration between school days and weekends was associated with increased impulsivity. 77 Further, one study conducted in 19 young adults showed that acute sleep restriction caused deregulation of cognitive control that may manifest in increased impulsivity. 78 …”
Section: Methodsmentioning
confidence: 99%